Android-Based Public Complaint Service System in Malimongan Tua Sub-district, Makassar - Resky Wahyuni; Marwa Sulehu; Tamus bin Tahir; Akbar Iskandar; Tatik Maslihatin; Tamra (Yayasan Cendekiawan Digital Indonesia, 2024)
The problem that occurs in the Public Complaints Service System in Malimongan Tua Village is the absence of a public complaint service system. Therefore, the researcher offers a solution to this problem by designing and implementing an Android-based public complaint service system. The purpose of this study is to design and implement an Android-based public complaint service system. Data were obtained through field research, library research, and interviews. The waterfall method is used in system development. The results of the study indicate that this data was obtained through observation, interviews, and library studies. The waterfall method is used in system development. The results of the study indicate that (the design and manufacture) of the Public Complaint Service System in Malimongan Tua Village, black box system testing ran well, and the results of User Acceptance Testing (UAT) testing on several respondents (Villages and Users) related to the use of the Android-based Public Complaint Service System Optimization application in Malimongan Tua Village, Makassar. In addition, the results of this study have been implemented in the form of community service, where this application helps the people of Malimongan Tua Village to convey their complaints more easily and efficiently, as well as improve the village government's response to problems faced by the community, it is concluded that this application is very suitable for use with a final score of 87.4%.